Egophoricity and Perspective: A View From Spoken Swedish - Bergqvist, Henrik (Frontiers in Communication, 2021)
From the point of view of everyday talk and especially, casual conversation, it is obvious that language use is highly perspectivized with a clear focus on the speech-act participants (e.g. Leech & Svartvik 2002). This fact is supported by observations regarding the pervasiveness of egophoric pronouns and the frequent use of the modal particles ju and väl in spoken Swedish (see Dahl 2000; Author 2020). The paper demonstrates how egophoric pronouns, modal particles, and mental verbs are used to signal the speech-act participants’ epistemic perspective, i.e. the knowledge and attention of the speech-act participants. These formally distinct resources show patterns of co-distribution that permits an analysis of forms in terms of how they signal shared/private access to events from the perspective of the speaker and the addressee.